Development of immobilized multipurpose biocatalyst from channel catfish (ictalurus punctatus) viscera using cross-linked enzyme aggregates (clea) technology - Mahmod, Safa Senan (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
Channel catfish (Ictalurus punctatus) viscera is considered as a daily produced waste that is discarded into water and land leading to serious environmental pollution. The visceral product is rich of enzymes that can be used in various applications. With the increase demand of biocatalysts in industry, a renewable and stable biocatalyst from an available source is required. Hence, cross-linking enzyme aggregate (CLEA) as immobilization method was used to prepare Multi-CLEA that consists of CLEA-lipase and CLEA-protease. In this study, the enzymatic activities of four selected hydrolases extracted from the fish viscera were investigated and the result showed that protease has the highest activity followed by cellulase, lipase and α-amylase. The effect of additives on CLEA preparation was studied and showed high effect of BSA on CLEA activity than SDS and heptane. Optimization was carried out in aqueous medium using ammonium sulfate as precipitant and organic solvent using acetone as precipitant. Response surface methodology (RSM) using faced centered composite design (FCCCD) was applied to study the interaction between the most contributing factors i.e. cross-linker, precipitant and additive concentrations. Optimum recovered activity for both CLEA-protease and CLEA-lipase was obtained in organic solvent with 33.24% and 125.67%, respectively. The produced multi-CLEA retained more than 28% of their initial activity after 6 batches of re-use. Furthermore, Michaelis-Menten kinetic models were used to determine the kinetic parameters (Km and Vmax) using Hyperbolic Regression Software (3.95), kinetic parameters for both CLEA-lipase and CLEA-protease obtained fitted Hanes-Woolf model. In order to prove that multi-CLEA produced can enhance many separate reactions, two applications were carried out at the end of this study. Multi-CLEA effect was evaluated based on its performance in a commercial detergent; results showed that the addition of multi-CLEA to a commercial detergent increased the percentage removal up to 60% as compared to the removal of the detergent itself for different food stains on a white cloth. Finally, enzymatic production of biodiesel was tested using multi-CLEA that was able to catalyze the esterification and transesterification reactions to produce biodiesel from vegetable cooking oil, with 51.7 % conversion of free fatty acid (FFA) into biodiesel. In conclusion, the development of this process would be an alternative source for immobilized protease and lipase production in large scale and cost effective in terms of using a wasteful by-product to produce a recyclable biocatalyst that has a wide range of applications.